The holy fool as a TV hero: about Pavel Lungin's film The Island and the problem of authenticity - Per-Arne Bodin (Journal of Aesthetics & Culture, 2011)
Holy foolishness (jurodstvo in Russian), a special monastic practice in the Orthodox Church, has become an important theme in the post-Soviet Russian culture. The example that perhaps has had the greatest impact is a feature film, Ostrov, The Island from 2006 directed by Pavel Lungin. The film tells the story of one fool in Christ, father Anatolij, who after committing a serious crime has become a monk in a small monastery in the Arctic. The film gives some examples of his provocative practice: clairvoyance, healing, and exorcism. What is demonstrated and interpreted is how an important phenomenon in the Russian Orthodox tradition is mediated, discussed, used, and changed in its new context. The material for the study is the film itself and the discussions around it in Russian mass media. The focus will be on the concept of authenticity. I argue that this concept has a crucial interpreting capacity for creating meaning in the film combining an Orthodox form of piety, a demand on art, and a crux in the postmodern condition.